Recycling of autoclaved aerated concrete in floor screeds: Sulfate leaching reduction by ettringite formation. (15th May 2016) - Bergmans, Jef; Nielsen, Peter; Snellings, Ruben; Broos, Kris
Highlights: Ettringite solubility controls sulfate leaching from products with recycled AAC. High pH conditions secure sulfate immobilisation. Recycled AAC aggregate can replace up to 40% of the sand fraction in floor screed. Abstract: Autoclaved aerated concrete (AAC) is a lightweight cellular concrete. Recycling AAC in concrete or unbound applications may cause problems because of high amounts of leachable sulfate. This study evaluates the recycling of AAC demolition waste as a replacement of sand in floor screed. The cement binder reacted with sulfate released from the AAC waste to form ettringite. Sulfate release was in line with ettringite solubility control and below leaching limits defined by Dutch environmental legislation. High pH conditions are necessary to avoid excessive sulfate leaching. Pollution of AAC waste with gypsum impurities was found to be detrimental to sulfate immobilisation.